From Evolutionary Aspects of Zoophytophagy to Biological Control - Dumont, François; Aubry, Olivier; Lucas, Eric (Frontiers in Ecology and Evolution, 2018)
Zoophytophagy (true omnivory) is a ubiquitous behaviour. It allows plant-feeding predators to maximize their development by finding essential nutrients, and to survive when animal resources are scarce. In agroecosystems, some zoophytophagous predators are highly efficient biological control agents. However, when feeding on plants, they can generate crop damage that reduce grower’s interest in these predators. Artificial selection on behavioural traits of candidate zoophytophagous predators could improve the ecosystem services they provide. Thus, a zoophytophagous species considered as noxious may become an adequate biocontrol agent, following a selection process. Numerous theoretical and applied aspects should be considered during the selection process for the breeding of desired individuals. This review focuses on the potential of the evolutionary approach to optimize the biological control services provided by plant-feeding predators – or zoophytophagous predators – and discuss some ecological and biological control consequences as well as the limitations of the approach.